PERSEPSI SISWA SMA TERHADAP PEMBELAJARAN YANG DIDUKUNG OLEH TEKNOLOGI KECERDASAN BUATAN (AI) - Octaviani, Ersa Indah; Fauzan, Ghifran Farosyi; Afifah, Hanna; Sari, Sandra Buana (CV. Jendela Gagasan, 2025)
This study aims to explore high school students’ perceptions of learning supported by artificial intelligence (AI) technology. The research is grounded in the growing integration of AI in post-pandemic education, which has significantly altered students’ learning habits. A mixed-methods approach was employed, combining online questionnaires from 30 students and literature review from five academic sources. The findings indicate that over 95% of students regularly use AI, which supports understanding complex materials, enhances task efficiency, and enables personalized learning. AI also boosts learning motivation through fast and interactive feedback. However, several challenges were identified, including dependency risks, reduced social interaction, inaccurate information, and potential plagiarism. Most students do not view AI as a teacher replacement, but rather as a complementary learning tool. This study concludes that AI integration in secondary education offers significant potential to improve learning quality, yet it must be balanced with digital literacy, ethical use, and the active role of teachers as facilitators.